Effects of Acupuncture-Point Stimulation on Perioperative Sleep Disorders: A Systematic Review with Meta-Analysis and Trial Sequential Analysis - Ying Liu; Yi Li; Meinv Liu; Meng Zhang; Jing Wang; Jianli Li (International Journal of Clinical Practice)
Background. Perioperative sleep disorders exert a severe adverse impact on postoperative recovery. Recently, some observational studies reported that acupuncture-point stimulation (APS) provided benefits for promoting perioperative sleep quality. However, the effects of APS on perioperative sleep disorders following general anesthesia have not been thoroughly assessed by any systematic study and meta-analysis. Therefore, we conducted this systematic review and meta-analysis to reveal the effects of APS on perioperative sleep disorders. Methods. Eight databases (Chinese: CNKI, VIP, CBM, and Wanfang; English: PubMed, Embase, Web of Science, and Cochrane Library) were thoroughly searched to find randomized controlled trials (RCTs) that indicated a link between APS and the occurrence of perioperative sleep disorders. We applied RevMan 5.4 (Cochrane Collaboration) and Stata 16.0 (Stata Corp) to conduct our meta-analysis. In addition, the trial sequential analysis (TSA) tool was utilized to estimate the validity and reliability of the data. Results. In this study, nine RCTs with 719 patients were conducted. Compared to the control group, APS significantly improved perioperative subjective sleep quality (SMD: −1.36; 95% CI: −1.71 to −1.01; P<0.00001). Besides, it increased perioperative TST (preoperative period MD = 24.29, 95% CI: 6.4 to 42.18, P=0.0008; postoperative period MD = 45.86, 95% CI: 30.00 to 61.71, P<0.00001) and SE (preoperative MD = 3.62, 95% CI: 2.84 to 4.39, P<0.00001; postoperative MD = 6.43, 95% CI: 0.95 to 11.73, P<0.00001). The consequence of trial sequential analysis further confirmed the reliability of our meta-analysis results. Conclusion. According to the currently available evidence, APS could effectively improve perioperative sleep quality and play an essential role in decreasing the incidence of perioperative sleep disorders.